Population-Based Study of Smoking Behaviour throughout Pregnancy and Adverse Perinatal Outcomes. - Murphy, Deirdre; Deane, Richard (My University, 2013)
There has been limited research addressing whether behavioural change in relation to smoking is maintained throughout pregnancy and the effect on perinatal outcomes. A cohort study addressed lifestyle behaviours of 907 women who booked for antenatal care and delivered in a large urban teaching hospital in 2010-2011. Adverse perinatal outcomes were compared for "non-smokers", "ex-smokers" and "current smokers". Of the 907 women, 270 (30%) reported smoking in the six months prior to pregnancy, and of those 160 (59%) had stopped smoking and 110 (41%) continued to smoke at the time of the first antenatal visit. There was virtually no change in smoking behaviour between the first antenatal visit and the third trimester of pregnancy. Factors associated with continuing to smoke included unplanned pregnancy (OR 1.9; 95% CI 1.3, 2.9), alcohol use (OR 3.4; 95% CI 2.1, 6.0) and previous illicit drug use (OR 3.6; 95% CI 2.1, 6.0). Ex-smokers had similar perinatal outcomes to non-smokers. Current smoking was associated with an average reduction in birth weight of 191 g (95% CI -294, -88) and an increased incidence of intrauterine growth restriction (24% versus 13%, adjusted OR 1.39 (95% CI 1.06, 1.84). Public Health campaigns emphasise the health benefits of quitting smoking in pregnancy. The greatest success appears to be pre-pregnancy and during the first trimester where women are largely self-motivated to quit.
PUBLISHED
Keywords: Pregnancy